Detection of Escherichia coli in Drinking Water Sources of Filter Units and Supply Water (Bangladesh Pharmaceutical Journal, 2016)
The identification of coliforms has been extensively used as an indicator of drinking water quality. The study was aimed to identify the presence or absence of E. coli from drinking water. Samples were collected from different filtration units and tap water sources of an institution in Dhaka city. All the samples were tested through presumptive, confirmed and completed bacteriological test through MPN (most probable number) using 3 sets of lactose broth (LB) media and MF (membrane filtration) technique using bacteriological filter and nutrient agar media to find out the CFU (colony forming unit). About 10% of samples showed positive results for E. coli in completed test, and also gave positive results in confirmed test and gram staining; having no more than 1100 MPN per 100 ml for samples of filter taps but the source water remained negative.Bangladesh Pharmaceutical Journal 19(2): 206-210, 2016